Insurance Products in Rastin Profit and Loss Sharing Banking - Bidabad, Bijan (Indian Journal of Finance and Banking, 2019)
Purpose: This paper aims to explain new insurance products and policies in Rastin Profit and Loss Sharing (PLS) Banking. Rastin Banking is a full Islamic Banking System with all necessary parts for banking operations that can be installed in conventional and Islamic banks both. In this paper, we are going to explain the milestones of new insurance products and policies.Design: Rastin Banking complies with the nature of the intermediary financial activity and has a new type of banking operations. The systems and instruments of this type of banking have different risk treatments, and new insurance policy and measures should be defined to cover the risks of the operations In order to fulfill this goal, appropriate insurance policies are described.Findings: Some new insurance products are defined such as Certificate Insurance, Insurance of Market Value of Certificate, Responsibility/Engineering Insurance, Insurance of Accidents Concerning the Article of Sharing, Collateral Insurance, Loss Margin Insurance, Profit Margin Insurance, Merchandise Transportation Insurance, Production Equipment and Installations Insurance, Product Quality Insurance, Insurance of Commodity under Production, Inventory Insurance, Production Limited Loss Insurance, Transaction Limited Loss Insurance to handle Rastin Banking.Research limitations: Many of these insurance policies are new and require more elaborations for further practical development and adjustment.Practical implications: These insurance products can be used both in Rastin Banking operations as well as conventional business and finance arrangements. These insurance policies have no conflict with indisputable legal principles, and insurance companies can supply these insurance products based on their own actuary calculations.Social implications: The introduced insurance policies actually change profit and loss sharing activity to just profit sharing.Originality/value: Approach of this system and the designed insurance policies is entirely different and new.